Penerapan Model Pembelajaran Make a Match dalam Meningkatkan Hasil Belajar Siswa - Riskiana Riskiana; Emmi Azis; Muhammad Yany (Journal on Education, 2025)
This research aims to improve student learning outcomes in economics subjects by using the make a match learning model. This research is classroom action research (PTK) which consists of two cycles, with each cycle including four stages: planning, implementation, observation, and reflection. The subjects of this research were 28 students in class X 4 of SMA Negeri 9 Bone. Data collection techniques used include observation, tests, and documentation, while data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this research show an increase in economic learning outcomes. In cycle I, 16 out of 28 students succeeded in achieving completeness with an average score of 73.25 and a completeness percentage of 57%, which was categorized as sufficient. In cycle II, the number of students who completed increased to 24 from 28 students with an average score of 84.28 and a completion percentage reaching 85%, which was categorized as very good. Based on these findings, it can be concluded that the make a match learning model is able to improve student learning outcomes in class X 4 economics subjects at SMA Negeri 9 Bone.